Implementasi Pendekatan CRT (Cullturally Responsive Teaching) untuk Meningkatkan Hasil Belajar Mata Pelajaran IPAS Kelas IV SDN 11 Mataram - Rabiatul Adawiyah; I Nyoman Karma; Diani Pratiwi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to improve the learning outcomes in Integrated Social and Natural Sciences (IPAS) of fourth-grade students at SD Negeri 11 Mataram on the topic Norms in My Life through the Culturally Responsive Teaching (CRT) approach. The research employed Classroom Action Research (CAR) consisting of two cycles, each conducted in one meeting. The study was carried out at SD Negeri 11 Mataram during the odd semester of the 2025/2026 academic year, involving 25 fourth-grade students as research participants. In Cycle I, only 56% of students achieved mastery of learning outcomes. This percentage increased significantly to 84% in Cycle II. Based on these findings, it can be concluded that the CRT approach is effective in improving students’ IPAS learning outcomes, particularly on the topic Norms in My Life.